2013
DOI: 10.1074/jbc.m113.478586
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Basis for the Regulation of the LIM-Homeodomain Protein Islet 1 (Isl1) by Intra- and Intermolecular Interactions

Abstract: Background: A putative intramolecular interaction in the Islet 1 (Isl1) transcription factor inhibits DNA binding. Results: An intramolecular interaction between the LIM domains and LIM homeobox 3 (Lhx3)-binding domain in Isl1 was characterized. Conclusion:The intramolecular interaction within Isl1 is weak but specific. Significance: This interaction likely prevents unproductive binding in the absence of cofactor proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 64 publications
(72 reference statements)
0
25
0
Order By: Relevance
“…In humans, LHX3 is broadly expressed in many tissues, including the pancreas. Although this particular transcription factor has not been previously reported to affect insulin secretory pathways, it does interact with several other transcription factors including insulin gene enhancer protein ISL1 and LIM homeobox transcription factor 1-alpha (LMX1A), which are known regulators of insulin gene expression [26].…”
Section: −5mentioning
confidence: 99%
“…In humans, LHX3 is broadly expressed in many tissues, including the pancreas. Although this particular transcription factor has not been previously reported to affect insulin secretory pathways, it does interact with several other transcription factors including insulin gene enhancer protein ISL1 and LIM homeobox transcription factor 1-alpha (LMX1A), which are known regulators of insulin gene expression [26].…”
Section: −5mentioning
confidence: 99%
“…The isolated LIM domains from these proteins tend to aggregate but can be stabilized by tethering the LIM domains to a LID, allowing their interaction to form soluble complexes. The thermofluor experiments are expected to report differences in folding and binding as LID sequences that bind more tightly should result in higher apparent melting point ( T m ) values, but only complexes that contain the same globular domain were compared to control for contributions of domain stability. These data indicated that the WT ISL2 binds LHX3/4 more tightly than does the mutant R282G, ~2°C higher T m for LHX4 and ~3°C for LHX3 (Supporting Information Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…For thermofluor experiments, purified LIM–LID fusion proteins were dialyzed (overnight at 4°C) into the same reservoir of 20 mM Tris (pH 8.0), 150 mM NaCl, 1 mM TCEP, and experiments carried out as described in Ref. with samples at 0.6 mg/mL protein. FRET‐based dilution experiments with 3C‐protease treated mYPet–LID–LIM 1 + 2 ‐mECFP fusion proteins were conducted as described previously, over the protein concentration range of 1‐9 μM.…”
Section: Methodsmentioning
confidence: 99%
“…However, Lim domains can also function as a protein-binding interface (36,89,(112)(113)(114)(115). The high-resolution structures of some of the Lim domains have been determined using nuclear magnetic resonance and X-ray crystallography, which suggests that the Lim domain zinc finger consists of two antiparallel β-hairpins with a short α-helix (78)(79)(80)82,(116)(117)(118)(119). The conserved cysteine/histidine/aspartate residues coordinate with the zinc atom which helps to maintain the secondary and tertiary structure of the Lim domains (28) (as depicted in Figure 2).…”
Section: Discussionmentioning
confidence: 99%